2019
DOI: 10.1002/nme.6256
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint Hamiltonian Monte Carlo algorithm for the estimation of elastic modulus through the inversion of elastic wave propagation data

Abstract: SUMMARY Efficient inversion of noisy seismic waveform data produced due to elastic wave propagation for the estimation of a high‐dimensional elastic modulus vector is achieved. Estimation is carried out in a Bayesian framework using Hamiltonian Monte Carlo (HMC) that enables efficient statistical estimation over high‐dimensional parameters. The truncated Karhunen‐Loève (K‐L) expansion is introduced to reduce the dimensionality of the elastic modulus vector. Expensive computations of the gradient of the state v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 76 publications
(154 reference statements)
0
13
0
Order By: Relevance
“…The computation of boldK0.16em1θ is straightforward and similar to the computations in Koch et al. 30 Considering the assembly K=eboldKe, where Ke is defined in (6), the derivatives at the elemental level can be given as boldKe1bold-italicθ=ΩeboldGnormalTke1θ,2θ1bold-italicθGJet¯dnormalΩe.Following the definition of k(bold-italicθ) in terms of the K1‐term truncated KL expansion in Equation (8), it is easy to get the derivatives as k1θq=λq2θboldΦq2θ.…”
Section: Simultaneous Update For Interface and Spatial Field Parametersmentioning
confidence: 88%
See 1 more Smart Citation
“…The computation of boldK0.16em1θ is straightforward and similar to the computations in Koch et al. 30 Considering the assembly K=eboldKe, where Ke is defined in (6), the derivatives at the elemental level can be given as boldKe1bold-italicθ=ΩeboldGnormalTke1θ,2θ1bold-italicθGJet¯dnormalΩe.Following the definition of k(bold-italicθ) in terms of the K1‐term truncated KL expansion in Equation (8), it is easy to get the derivatives as k1θq=λq2θboldΦq2θ.…”
Section: Simultaneous Update For Interface and Spatial Field Parametersmentioning
confidence: 88%
“…these large parameter vectors further adds to the computational demands. The adjoint based HMC method, 30 that uses dimensionality reduction and the adjoint method to promote computational efficiency solves these issues. Citing these advantages, this paper proposes a method to combine the explicit interface detection strategy of HMCID with the adjoint based HMC method for spatial field estimation to simultaneously estimate interface and spatial fields.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the geometry and spatial parameters due to the domain of definition of the IEVP is also detailed. It should be noted that the procedure detailed above is applicable to both the direct differentiation and adjoint methods [9] of sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Koch et al. developed Hamiltonian Monte Carlo (HMC) algorithm to efficiently estimate the elastic modulus through the inversion of elastic wave propagation data (Koch et al. , 2020a), and the solid-void interface through elastodynamic inversion (Koch et al.…”
Section: Introductionmentioning
confidence: 99%
“…Cooreman et al (2007) identified the metal's physical property parameters during plastic deformation by comparing an experimentally measured strain field with computed data from a finite element model, and an analytical method was used to calculate the sensitivity coefficients. Koch et al developed Hamiltonian Monte Carlo (HMC) algorithm to efficiently estimate the elastic modulus through the inversion of elastic wave propagation data (Koch et al, 2020a), and the solid-void interface through elastodynamic inversion (Koch et al, 2020b). Moreover, they also used the method to simultaneously identify the interface and spatial field properties through the inversion of hydraulic head and discharge rate data obtained from a steady seepage flow experiment on a domain containing a predefined piping zone (Koch et al, 2021).…”
Section: Introductionmentioning
confidence: 99%